Acute kidney injury due to tubular intraluminal monoclonal light chain crystals mimicking acute pyelonephritis. (March 2014) - Haider, Mumnoon; Salvatore, Steven P.; Kaplan, Joshua; Seshan, Surya V.
Abstract Tubular intraluminal inflammatory cells may be seen in kidney biopsies of patients with pyelonephritis, cell-mediated transplant rejection, autoimmune tubulointerstitial nephritis, allergic reactions, or in association with monoclonal light chain casts. When casts in a native kidney are primarily composed of granulocytes, the cause is most commonly acute pyelonephritis due to an ascending bacterial urinary tract infection. We report a 57-year-old man with acute kidney injury and an intense intraluminal neutrophil response to monoclonal lambda light chain crystal containing casts.